KENDALI PID PADA QUADCOPTER UNTUK GERAK ATTITUDE PITCH DAN ROLL SAAT HOVERING - Nugroho, Agung; Khairurozi, Haris; Suprijono, Herwin; Heryanto, M Ary (Universitas Semarang, 2024)
The quadcopter represents one of the emerging research areas in unmanned aerial vehicle (UAV) technology. One of its advantages lies in its simple mechanism and smaller propeller size compared to helicopters, while maintaining the same lifting capacity. The quadcopter employs inner and outer control schemes, where the inner control manages attitude roll, pitch, yaw, and altitude, thereby affecting the motion of the quadcopter. Meanwhile, the outer control governs the direction of the quadcopter's movement. This condition underscores the significance of inner control, ensuring the quadcopter's maneuverability. Consequently, there is a need to design an attitude, pitch, and roll control using the PID method. This experiment focuses on roll and pitch control under hover conditions. The PID control experiment yielded optimal results with parameters KP = 60, KI = 22, and KD = 14, exhibiting rapid response, absence of oscillation, deviations smaller than 20o in both roll and pitch controls, and the ability to return the attitude to the initial setpoint position when disturbances occur. Keywords: Attitude, hovering, PID controller, quadcopter. ABSTRAKQuadcopter merupakan salah satu bidang riset yang baru dalam teknologi unmanned aerial vehicle (UAV). Salah satu keunggulan pada Quadcopter adalah mekanisme yang sederhana dan ukuran pada baling-baling yang lebih kecil dibandingkan dengan helicopter dengan daya angkat yang sama. Quadcopter memiliki skema kendali inner dan kendali outer, dimana kendali inner mengendalikan attitude roll, pitch, yaw, dan altitude yang berimplikasi pada gerak quadcopter. Sedangkan kendali outer mengendalikan arah gerak quadcopter. Kondisi ini menjadikan kendali inner sangat penting sehingga mampu menjaga quadcopter dapat bergerak. Untuk itu perlu dirancang suatu kendali attitude pitch dan roll dengan metode PID. Eksperimen ini focus pada kendali roll dan pitch di kondisi hover. Hasil eksperimen kendali PID pada roll dan pitch didapatkan hasil terbaik pada parameter KP=60, KI=22, dan KD=14 yang memiliki respon cepat, tidak terjadi osilasi, lonjakan lebih kecil dari 20o baik pada kendali roll maupun pitch, dan mampu mengembalikan attitude pada posisi setpoint awal apabila diberi gangguan.